2015
DOI: 10.1039/c5ta04642d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tri-level hierarchical SAPO-34 zeolite with intracrystalline micro–meso–macroporosity showing superior MTO performance

Abstract: ‡ These authors contributed equally. Electronic Supplementary Information (ESI) available: [TG curves and the detailed MTO results over SAPO-34 catalysts, etc. are provided in the supporting information.]. SeeHierarchically porous zeolites with different level of porosity have emerged as an important class of materials because of their enhanced mass transport and improved catalytic performance. Silicoaluminophosphate zeolite SAPO-34 is one of the best catalysts for methanol-to-olefin (MTO) conversion, but suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(63 citation statements)
references
References 47 publications
6
57
0
Order By: Relevance
“…However, a slight decrease can be seen in the concentration of the strong acid sites with the addition of PEG, which is the same result that was reported in Ref. [31]. Therefore, the longer the chain of PEG is, the fewer strong acid sites will occur.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, a slight decrease can be seen in the concentration of the strong acid sites with the addition of PEG, which is the same result that was reported in Ref. [31]. Therefore, the longer the chain of PEG is, the fewer strong acid sites will occur.…”
Section: Resultssupporting
confidence: 87%
“…The BET specific surface areas, micropore surface areas, and micropore volumes of the samples are listed in Table 1. It can be observed that all the samples present type I isotherms according to the IUPAC classification [31,32]. With the addition of PEG, the external surface area of the samples increased, but the micropore surface area almost have no change.…”
Section: Resultsmentioning
confidence: 93%
“…The microporous sample S M ‐4.0 and hierarchical samples S H ‐4.0, S H ‐3.0, S H ‐2.0, and S H ‐1.6 displayed characteristic type‐I N 2 adsorption–desorption isotherms (Figure a). Compared with sample S M ‐4.0, an apparent uptake near the saturation pressure in the isotherms of all hierarchical SAPO‐34 samples was observed, which was attributed to the presence of voids between the stacked nanometer‐sized crystals and the existence of mesopores or macropores in the hierarchical SAPO‐34 crystals . This was in accordance with the SEM and TEM images.…”
Section: Resultssupporting
confidence: 84%
“…Notably, the nanometer‐sized hierarchical catalyst S H ‐3.0 had the longest catalytic lifetime of 366 min and the highest selectivity of ethylene plus propylene of up to 85.4 %, which were much higher than those of the microporous catalyst S M ‐4.0 (126 min, 79.7 %) and other hierarchical catalysts S H ‐4.0 (326 min, 84.9 %), S H ‐2.0 (326 min, 82.4 %), and S H ‐1.6 (306 min, 78.1 %). The MTO catalytic performance of the catalyst S H ‐3.0 was the highest level reported for MTO reactions under similar conditions . More importantly, under the same catalytic conditions (450 °C, WHSV=4 h −1 ) as our previous work, the S H ‐3.0 catalyst possessed more than 40 % decreased consumption of organic template and 0.7 % enhanced selectivity of ethylene and propylene (the detailed catalysis results of our previous work are shown in Table and Figure S10 in the Supporting Information) …”
Section: Resultssupporting
confidence: 60%
“…Methanol to lower olefins reaction is a critical process for conversion of nonoil resources to chemicals through methanol, and light olefins especially ethylene and propylene have been widely applied in polymerization reaction and petrochemical industry [1][2][3][4][5][6]. Several types of molecular sieves for the MTO reaction have been intensively studied, and the most typically are SAPO-34 [7,8], ZSM-5 [9][10][11], and SSZ-13 [12][13][14]. Among these catalysts, SAPO-34 has drawn the most attention due to its special framework with a CHA cage (9.4 Å) and 8-ring pore openings (0.38 Å 0.38 Å) [15], as well as mild acidity [16][17][18] which result in excellent catalytic performance [3,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%